HETEROGLOSSIA IN SOPHIE KINSELLAâS THE UNDOMESTIC GODDESS - ., Yulistiyanti (Proceeding SENDI_U, 2016)
This study reveals the differentiated languages or heteroglossia in popular novel entitled The UndomesticGoddess. Heteroglossia is a terminology which Mikhail Bakhtin introduced in his essay Discourse in theNovel. Novel is an arena where the contestation of ideologies take place. It contests from the socialinteraction among the characters of a novel. The Undomestic Goddess tells about a young female lawyerwho gets fired from the law firm because she makes a huge mistake, then because of the mistake shebecomes a house-keeper. Heteroglossia is applied in this novel known from the utterances used by thecharacters and narrator of the novel. From heteroglossia or differentiated languages emanate ideologies.This study focuses on the contestation of the two opposite ideologies; patriarchy and feminism. Itidentifies utterances and categorizes them. It also needs interpretation to elucidate the ideologies found inthe utterances. Patriarchal ideology which has put male as a dominant force is not only believed by themale characters, but the female characters also practise them. The opposite ideology, feminism shows thatthe female character tries to break the social construction that brings female as an important other andoften gets discrimination in the binary opposition between male and female. This novel depicts the socialproblem people experience although they live in this modern era when digital technology cannot beseparated from their lives and females can achieve high-education and do career, the patriarchal ideologystill works in the society.Keywords: heteroglossia, patriarchy, feminism, ideological contestation, The Undomestic Goddess